2015
DOI: 10.1007/s10340-015-0711-x
|View full text |Cite
|
Sign up to set email alerts
|

Strong synergistic activity and egg hatch inhibition by (E,E)-2,4-decadienal and (E)-2-decenal in Meloidogyne species

Abstract: Recent research has been focused on the potential of plant natural products for the control of nematodes, but few studies are reported on synergistic interactions and egg hatch inhibition properties of botanicals. Herein, we evaluate the nematicidal activity of (E,E)-2,4-decadienal, 2-undecanone, furfural and (E)-2-decenal alone and in binary mixtures, on different Meloidogyne spp. and growth stages. (E,E)-2,4-decadienal exhibited strong paralysis activity on second-stage M. incognita,M. javanica and M. arenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…2-Phenylacetic acid was found to have effective antibacterial activity against Escherichia coli and Ralstonia solanacearum (Zhu et al, 2011 ). ( E,E )-2,4-Decadienal exhibited strong paralytic activity on second-stage Meloidogyne incognita, Meloidogyne javanica and Meloidogyne arenaria juveniles (Ntalli et al, 2016 ). Guan et al ( 2016 ) reported benzeneacetamide as an antidepressant-like and anticonvulsant compound.…”
Section: Discussionmentioning
confidence: 99%
“…2-Phenylacetic acid was found to have effective antibacterial activity against Escherichia coli and Ralstonia solanacearum (Zhu et al, 2011 ). ( E,E )-2,4-Decadienal exhibited strong paralytic activity on second-stage Meloidogyne incognita, Meloidogyne javanica and Meloidogyne arenaria juveniles (Ntalli et al, 2016 ). Guan et al ( 2016 ) reported benzeneacetamide as an antidepressant-like and anticonvulsant compound.…”
Section: Discussionmentioning
confidence: 99%
“…While spore suspensions of S. monomycini ATHUBA 220 and S. colombiensis ATHUBA 438 could alleviate the nematode burden of M. incognita in Col-0 and fra2 ( Figure 3 A) respectively, to our surprise, this was not the case for M. javanica , where S. colombiensis ATHUBA 438 and S. monomycini ATHUBA 220 were ineffective ( Figure 3 B). Additionally, it has previously been demonstrated that M. javanica is more difficult to control than M. incognita [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…2-methyloctacosane has antimicrobial properties against A. flavus, C. albicans, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus (Barretto & Vootla, 2018). A study conducted by Ntalli et al (2016) reported that 2,4-decadienal, (E,E)-showed strong activity against Meloidogyne arenaria, Meloidogyne incognita and Meloidogyne javanica parasitic nematodes and promoted tomato growth. Based on our knowledge, this is the first time that volatile compounds produced by fungal endophytes from S. mauritianum Scop.…”
Section: Comparison Of Volatile Metabolites Harvested In Winter and Summermentioning
confidence: 99%